Social Innovation, Gender, and Technology: Bridging the Resource Gap - Warnecke, Tonia (Journal of Economic Issues (Taylor & Francis Ltd), 2017)
Some of the most important resources are intangible, such as knowledge and access to networks. In the developing world, technology can facilitate these resources and address basic human needs in a variety of ways: from provision of farmer training and cloud-controlled clean water systems to health information and mobile money services. Some of these services expand access to resources in ways that particularly benefit women. In environments where women are disadvantaged socially and economically, information and communications technologies (ICT) can enable women to access valuable information, consider a broader range of business opportunities, access wider markets, partake in educational programs, and share experiences with and gain mentorship from other women. However, there are large gender gaps in the access to technology, particularly in rural areas. To begin, I briefly discuss the role of technology in development, and consider the extent and significance of technology gender gaps. Next, I review key barriers to reducing these gaps, and discuss the concept of social innovation as it applies to technology interventions. Examples from five social innovations in India — a country with large technology gender gaps — illustrate the range of possibilities for innovative access to and use of ICT for diverse target groups. I conclude with some suggestions for further improvement in this area.
Number: 2 Publisher: Taylor & Francis Ltd
Keywords: Réservé UdeM